Synthesis and Microstructural Characterization of Lanthanum Doped Cerium Oxide by Solution Combustion Synthesis - Evandro Garske Scarabelot; Vânia Caldas de Sousa; Luís Alberto Loureiro dos Santos Almeida; Willians Lopes de Almeida; José Jurado Egea (Materials Research)
Materials based on doped ceria are considered promising elements for applications in solid oxide fuel cells (SOFCs). Cerium oxide can be classified as a mixed conductor. The type of dopant also greatly influences properties of doped ceria. Hence, studying the type of dopant to be used in the synthesis process is of great importance. Recent studies have shown that the lanthanide or alkaline earth ions are the most commonly dopants used in ceria. In order to obtain nanometric powders, which favor the catalytic effect and are more reactive than other powders, a technique of obtaining powders via solution combustion synthesis (SCS) was selected, and the type of fuel used, and its excess (content) were analyzed. The parameters that were varied in this study were related to the dopant (Ce(1-x) La(x) O(2- δ), where x = 0.1, 0.2, 0.3) and the type of fuel used (urea or sucrose) The powders were characterized by thermogravimetric analysis (TGA), X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). In the TGA, a significant increase in the remaining mass loss was observed with an increase in the dopant content when both urea and sucrose were used. The SCS method enabled the production of lanthanum oxide doped ceria phase using both fuels. The XRD of the samples obtained using urea as fuel exhibited well-defined, narrow, and intense peaks immediately after synthesis, and this characteristic was maintained after thermal treatment. On the other hand, the use of sucrose as fuel enables the production of the same cristalinity after thermal treatment at 850°C. In addition, these samples had a higher specific surface area and smaller crystallite size compared to those obtained using urea as fuel.